2017
DOI: 10.12965/jer.1734990.495
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of alpha band of the electroencephalogram before and after a task of proprioceptive neuromuscular facilitation

Abstract: The proprioceptive neuromuscular facilitation (PNF) sets up a feature of treatment developed with the objective to facilitate and improve the motor performance. The aim of this study was to investigate in healthy female individuals the effects of electrophysiological of a diagonal of the PNF upper limb. The sample consisted of 30 female participants aged between 18 to 28 years, randomly divided into 3 groups (G1, G2, and G3). The three groups had 2 moments of electroencephalographic signal detection, before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…PNF technique emphasizes diagonal movement according to the patient’s rehabilitation goals. Here, the patient controls and relaxes, enhancing their ability to recover their perception and control of the diseased area [ 28 , 29 ]. PNF technique was also able to closely restore patients’ daily living ability, thus mobilizing their recovery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNF technique emphasizes diagonal movement according to the patient’s rehabilitation goals. Here, the patient controls and relaxes, enhancing their ability to recover their perception and control of the diseased area [ 28 , 29 ]. PNF technique was also able to closely restore patients’ daily living ability, thus mobilizing their recovery [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…PNF technique introduces resistance training, where patients need to coordinate their overall structure and movement to resist the motion given. This training can mobilize the diseased tissues so that that they could be restored through gradual training [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 - 16 ] Proprioceptive neuromuscular facilitation was primarily developed by Dr. Herman Kabat and his collaborators in 1940s[ 17 ] and is used for numerous neurologic and musculoskeletal diseases. [ 18 ] It was reported that PNF could promote neuromuscular responses through stimulating proprioceptors,[ 19 , 20 ] improve muscular strength,[ 21 , 22 ] joint stability, mobility,[ 23 - 27 ] neuromuscular control, and coordination, consequently improving the overall functional ability of patients with CLBP. [ 28 - 30 ] However, the evidence on PNF for the management of CLBP is not sufficient.…”
Section: Introductionmentioning
confidence: 99%